Formulation of maintenance program for G-Liner - Caballes, Christian Frederick (College of Engineering, 2005)
Maintenance is extremely important in a bus company such as G-liner. Buses are the focal point of the company's operation, thus it is crucial that they have an effective maintenance program so that buses are operating at all times. Bus breakdowns mean loss of income and repair cost. At present, G-liner experiences considerably large number of breakdowns. It is in this light that the group finds it worthy to apply the methods and techniques of Operations Management to reduce the breakdowns and generate recommendations to improve the company's maintenance system. The group limits its study on operating air conditioned buses of age 7-15 years old since 80% of the breakdowns come from this type of buses. Using Pareto chart, the group identified the three most costly breakdowns to address. These major breakdowns are on engine, transmission and differential. The company spends an average of P 5,091,522 per year on breakdown maintenance and P3,876,680 per year on preventive maintenance for the mentioned parts. Breakdown maintenance deals with breakdowns when they occur while preventive maintenance seeks to reduce breakdowns. To save time and minimize cost, employing only one type of maintenance is feasible. From the expected number of breakdowns, the expected cost of repair without preventive maintenance is determined. It was assumed that if preventive maintenance is performed, the probability of breakdown is negligible. The results showed that preventive maintenance is cheaper to use compared to breakdown maintenance. Thus the group recommends that G0Liner should employ preventive maintenance. The group further determined the optimal maintenance schedule using predictive maintenance. The recommended schedule, if implemented would yield a savings of P 539,555.40 per month or equivalently, P6,474,665 annually.